THE MEDIATING ROLE OF JACOBSON RELAXATION TECHNIQUES IN THE RELATIONSHIP BETWEEN ANXIETY AND PERFORMANCE OF FEMALE HANDBALL PLAYERS - Raluca Maria PETRUȘ; Maria Daniela MACRA-OȘORHEAN; Paul Ovidiu RADU; Rodica Cristina PETRUȘ (Cluj University Press, 2022)
One of the most discussed relationships in sport psychology is the relationship between competitive anxiety and sport performance. The issues addressed in this paper refer to the affective state of female competitive players and its link to the effectiveness/achievement of their long-term game. Objectives: The current work aimed to study how a high degree of anxiety affects the playing efficiency of the SCM Gloria Buzău handball team and to what extent the level of anxiety and, implicitly, of performance, can be modified in a beneficial way, by using the Jacobson technique. Methods and means: To carry out this study, the SAS-2 questionnaire, a multidimensional instrument that measures cognitive and somatic characteristics related to anxiety, was applied in the context of practicing performance sports. To analyse the data obtained, the SPSS Statistics V.20 analysis software was used, thus performing a multiple regression analysis, with anxiety as a predictor and efficiency as a criterion. In order to capture the effect of the Johnson method on the athletes' performance, a two-way mixed ANOVA analysis of the 2x2 type was used. Results: Following this analysis, the following aspects can be noted: efficiency and anxiety correlate strongly, in the opposite direction, with a negative correlation coefficient between the two variables, r = -0.902. This correlation has high statistical significance (sig<0.001). We observed that there is a strong, positive correlation between the level of control of emotions acquired as a result of therapy and the level of performance in the game, r=0.96, the result being statistically significant, sig<0.001. Conclusions: The hypothesis on how a certain relaxation technique, applied in a consistent manner over a sufficient period of time, leads to an improvement in the quality of the athletes' game was confirmed. Thus, following Jacobson relaxation techniques applied on female handball players, an increase in performance level was observed in both anxious and low-anxious individuals.   REZUMAT. Rolul mediator al tehnicilor de relaxare jacobson în relația dintre anxietate și performanța jucătoarelor de handbal. Una dintre cele mai discutate relații în psihologia sportului este relația dintre anxietatea competitivă și performanța sportivă. Problemele abordate în această lucrare se referă la starea afectivă a jucătoarelor competitive și legătura acesteia cu eficacitatea/realizarea jocului pe termen lung. Obiective. În această cercetare, autorii, și-au propus să studieze modul în care un grad ridicat de anxietate afectează eficiența jocului echipei SCM Gloria Buzău și în ce măsură nivelul de anxietate, și implicit, de performanță, poate fi modificat în mod benefic prin utilizarea metodei Jacobson. Metode și mijloace. Pentru realizarea acestui studiu a fost aplicat în contextul practicării sporturilor de performanță chestionarul SAS-2, un instrument multidimensional care măsoară caracteristicile cognitive și somatice legate de anxietate. Pentru analiza datelor obținute s-a utilizat software-ul de analiză SPSS Statistics V.20, realizându-se astfel o analiză de regresie multiplă, cu anxietatea ca predictor și eficiența ca și criteriu. Pentru a surprinde efectul metodei Johnson asupra performanței sportivilor, a fost utilizat testul de analiză ANOVA mixtă bidirecțională de tip 2x2. Rezultate. În urma acestei analize se remarcă următoarele aspecte: eficiența și anxietatea se corelează puternic, în sens invers, cu un coeficient de corelație negativ între cele două variabile, r = -0.902. Această corelație are o semnificație statistică puternică (sig. < 0.001). Am observat că există o corelație puternică, pozitivă, între nivelul de control al emoțiilor dobândit în urma terapiei și a nivelului de performanță în joc, r = 0.96, rezultatul fiind semnificativ statistic (sig. < 0.001). Concluzii. S-a confirmat faptul că o anumită tehnică de relaxare, aplicată în mod consecvent pe o perioadă suficientă de timp, conduce la o îmbunătățire a calității jocului sportivilor. Astfel, în urma tehnicilor de relaxare Jacobson aplicate pe jucătoarele de handbal, s-a observat o creștere a nivelului de performanță atât la sportivele anxioase, cât și la cele cu o anxietate mai scăzută. Cuvinte cheie: anxietate, performanță, handbal, metoda Jacobson. Received: 2022 March 04; Revised: 2022 April 11; Accepted: 2022 April 11; Available online: 2022 March 30; Available print: 2022 May 30.